Prospects for Knockout of MYB60, a Transcriptional Repressor of Anthocyanin Biosynthesis, in Brassicaceae Plants by Genome Editing - Mikhaylova, Elena; Artyukhin, Alexander; Shein, Michael; Musin, Khalit; Sukhareva, Anna; Kuluev, Bulat (KnE Life Sciences, 2022)
The Brassicaceae plant family contains many economically important crops such as Brassica napus L., Brassica rapa L., Brassica oleracea L., Brassica juncea L., Eruca sativa Mill., Camelina sativa L. and Raphanus sativus L. Insufficient data on the genetic regulation of agronomic traits in these species complicates the editing of their genomes. In recent years, the attention of the academic community has been drawn to anthocyanin hyperaccumulation. This trait is not only beneficial for human health, but can also increase plant resistance to stress. MYB transcription factors are the main regulators of flavonoid biosynthesis in plants. Some of them are well studied in Arabidopsis thaliana. The AtMYB60 gene is a transcriptional repressor of anthocyanin biosynthesis, and it also negatively impacts plant responses to drought stress. Myb60 is one of the least studied transcription factors with similar functions in Brassicaceae. There is a high degree of homology between predicted MYB60 genes of A. thaliana and related plant species. However, functions of these homologous genes have never been studied. Gene knockout by CRISPR/Cas technology remains the easiest way to perform genome editing in order to discover the role of individual plant genes. Disruption of genes acting as negative regulators of anthocyanin biosynthesis could result in color staining of plant tissues and an increase in stress tolerance. In the present study, we investigated the AtMYB60 gene and its homologs in Brassicaceae plants and suggested universal gRNAs to knockout these genes. Keywords: CRISPR, Brassicaceae, MYB60, knockout, anthocyanin